Thermal overload tests on a 400-MVA power transformer with a special 2.5-p.u. Short time loading capability. - Nordman, H. (IEEE Transactions on power delivery)
Comprehensive load /thermal testing was performed on a 400/400/125-MVA transformer representing a new design generation for large power transformers with a short time emergency loadability of 2.5 p.u. This particular overloadability factor required special design features to control the very high leakage flux resulting from such a loading condition and hence ensure that the transformer satisfies existing standards limits on hot-spot. This paper presents these design features along with a description of a full-size transformer which was built for the sake of developing these flux control measures. Hot-spot temperature measurements in the windings and in the outer core packets and structural parts under a number of overloading conditions are presented and discussed. The results confirm the soundness of the design to handle the 2.5-p.u. overloadability while satisfying the hot-spot requirement according to the existing loading guides for 1.5-p.u. overloading. The measurements also show that the hot-spots will rise much faster than what an exponential function based on the time constant of top oil would predict.